Immunomodulatory oligonucleotide IMT504: effects on mesenchymal stem cells as a first-in-class immunoprotective/immunoregenerative therapy - Zorzopulos, Jorge (2017)
The immune responses of humans and animals to insults (i.e., infections, traumas, tumoral transformation and radiation) are based on an intricate network of cells and chemical messengers. Abnormally high inflammation immediately after insult or abnormally prolonged pro-inflammatory stimuli bringing about chronic inflammation can lead to life-threatening or severely debilitating diseases. Mesenchymal stem cell (MSC) transplant has proved to be an effective therapy in preclinical studies which evaluated a vast diversity of inflammatory conditions. MSCs lead to resolution of inflammation, preparation for regeneration and actual regeneration, and then ultimate return to normal baseline or homeostasis. However, in clinical trials of transplanted MSCs, the expectations of great medical benefit have not yet been fulfilled. As a practical alternative to MSC transplant, a synthetic drug with the capacity to boost endogenous MSC expansion and/or activation may also be effective. Regarding this, IMT504, the prototype of a major class of immunomodulatory oligonucleotides, induces in vivo expansion of MSCs, resulting in a marked improvement in preclinical models of neuropathic pain, osteoporosis, diabetes and sepsis. IMT504 is easily manufactured and has an excellent preclinical safety record. In the small number of patients studied thus far, IMT504 has been well-tolerated, even at very high dosage. Further clinical investigation is necessary to demonstrate the utility of IMT504 for resolution of inflammation and regeneration in a broad array of human diseases that would likely benefit from an immunoprotective/immunoregenerative therapy.